answersLogoWhite

0


Best Answer

2a + 3a + 4 = 5a + 4

User Avatar

Wiki User

โˆ™ 2010-04-02 20:07:34
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides
๐Ÿ““
See all Study Guides
โœ๏ธ
Create a Study Guide

Add your answer:

Earn +20 pts
Q: Simplify 2a plus 3a plus 4 equals?
Write your answer...
Submit
Related questions

A plus a plus a-2a equals?

a + a + a - 2a = 3a - 2a = a


-a plus 3a-2a equals?

1


Simplify 3aยฒ plus a-aยฒ plus 5a?

2a² + 6a


What is the answer to Simplify 5a plus 4b-3a?

2a + 4b


Simplify 3a plus 5 plus 2a plus 6?

5a + 11


What is -2a plus 3a plus 5b?

What is the solution of -2a plus 3a plus 5b


What does 3a plus 2a equal?

3a + 2a = 5a


What does 2a plus 5a plus 3a equal?

2a + 5a + 3a = 10a


How do you solve -2a plus 5 plus 3a equals 15-21?

depends what 'a' =


What does a plus 2a plus an equal?

2a + a = 3a


3a plus 3b-2a plus 5b?

3a + (3b - 2a) + 5b =3a + 3b - 2a + 5b =(3a - 2a) + (3b + 5b) =a + 8b


What is 3a plus b-2a plus b?

1


Simplify the expression 3a plus 2b - c - 2a plus 5b plus 3c by combining like terms?

a + 7b + 2c


3a plus 5 equals 5a plus 3?

If 3a+5=5a+3, then: 3a+5 - 3a = 5a+3 - 3a 5=2a+3 5 - 3=2a+3 - 3 2=2a a=1


What is the answer to 3a plus 4?

3a plus 4 equals 3a +4. You can not combine the two parts because they are not like terms so there is no way to simplify this.


Can someone Simplify the expression 3a plus 2b - c - 2a plus 5b plus 3c by combining like terms?

ok, let's see: (3a-2a) + (2b+5b) +(-c +3c) = a + 7b +2c I think that's right.


How do yo solve 2a-24-3a equals 5a?

3a x 2a =24


What is the solution to a equals 3a plus 4?

a = 3a + 4 0 = 2a + 4 2a = -4 a = -2


What is the answer to 2a plus a?

3a


How do you simplify 3a plus 2b - a plus 4b?

Change the order to make it more obvious: 3a - a + 2b + 4b 2a + 6b or 2 (a + 3b).


Factor 2a squared plus 3a plus 1?

(2a+1)(a+1)


What is the correct answer when you factor 6a2 plus 3a?

3a(2a + 1)


What is 3a-2a?

3a-2a = 1


Is a plus 2a equals 3a equation or expression?

It is, in fact, an identity - which is an equation which is true for all values of the variable.


3a(a plus 4)-2a plus 7?

It can be simplified to: 3a^2 +10a+7 or factored as (3a+7)(a+1)